Con: The role of diet for people with advanced Stage 5 CKD. (19th February 2018) - Woodrow, Graham
Abstract: Restriction of dietary protein intake has been used in the management of chronic kidney disease (CKD) for many decades, yet remains controversial, with marked variations in its application in clinical practice. There is extensive literature on the subject, with some expert opinion advocating the use of protein restriction based on the balance of the available evidence. The largest randomized trial of low-protein diets is the Modification of Diet in Renal Disease study. Despite multiple secondary analyses, the essential intention-to-treat analysis failed to demonstrate a benefit in the primary outcome of rate of decline of glomerular filtration rate. There are criticisms of many published studies and meta-analyses, including the likelihood of publication bias and unsuitable biochemical endpoints that may be affected by dietary restriction in the absence of effects on kidney function, leading to false positive findings. It is also uncertain whether any benefits observed in these often older studies would be derived in patients undergoing modern standards of CKD management, including blood pressure control and renin–angiotensin blockade. Thus it is unclear whether, even in the strictly controlled environment of a clinical study, low-protein diets significantly slow CKD progression. Important questions exist regarding the applicability of these diets in routine clinical practice. Even in carefully selected study populations with intensive dietetic input, adherence to low-protein diets is poor. It is likely that only a small minority of CKD patients in routine practice could adhere to these diets, and although risks of malnutrition arising from protein restriction are uncertain, they will be greater in less supervised care outside of studies.